Maya Angelou’s Poems “Still I Rise” and “Woman Work”: Voices of Defiance on Female Violence and Resistance - Suhadi, Agung (Teaching English and Language Learning English Journal, 2024)
This article explores the complex portrayal of female violence and resistance in Maya Angelou’s poetry. By examining key poems, this study uncover how Angelou addresses the dynamics of power, suffering, and resilience, highlighting the poet’s unique voice in confronting and transcending the violence experienced by women. Her poems "Still I Rise" and "Woman Work" provide powerful examinations of female violence and resistance, highlighting the resilience and strength of women facing systemic and personal adversities. In "Still I Rise," Angelou portrays an unyielding spirit in the face of oppression and dehumanization. The poem's repeated affirmation of rising above derogatory treatment and emotional abuse exemplifies a profound resistance to societal constraints. Similarly, "Woman Work" underscores the relentless labor performed by women, including physical, emotional, and spiritual dimensions. Through the imagery of caregiving and repetitive tasks, Angelou illustrates how women’s work is a form of resistance against undervaluation and neglect. In shorts, both poems celebrate the capacity for joy and self-assertion amidst struggle, reinforcing the themes of empowerment and defiance.